2012
DOI: 10.1108/08876041211215275
|View full text |Cite
|
Sign up to set email alerts
|

The role of cause and affect in service failure

Abstract: PurposeThe primary purpose of this paper is to explore the role of emotions that consumers experience as a result of assigning causal attributions to service failures. The secondary purpose is to consider the effects of each of these emotions on behavioral outcomes.Design/methodology/approachThis paper extends the work of Wetzer, Zeelenberg, and Pieters regarding emotions and draws upon the existing literature to present a series of research propositions tying attributions to emotions and emotions to behaviora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 47 publications
0
70
0
3
Order By: Relevance
“…Moreover, work has shown that attributing an outcome (i.e., falling) on the dimension of controllability (i.e., being ill vs. being drunk) can lead to feelings such as pity or anger, which subsequently motivate either supportive or nonsupportive responses (Morales 2005;Weiner 1995). The majority of work on attributions in service failure contexts supports the notion of a pathway through anger (Bonifield and Cole 2007;Folkes, Koletsky, and Graham 1987) leading to retaliatory behavior (Andreassen 1999;Harrison-Walker 2012). To our knowledge, existing work has not examined how attributions may influence positive reactions to firms, such as increased empathy or compassion.…”
Section: Perceptions Of Fairnessmentioning
confidence: 99%
“…Moreover, work has shown that attributing an outcome (i.e., falling) on the dimension of controllability (i.e., being ill vs. being drunk) can lead to feelings such as pity or anger, which subsequently motivate either supportive or nonsupportive responses (Morales 2005;Weiner 1995). The majority of work on attributions in service failure contexts supports the notion of a pathway through anger (Bonifield and Cole 2007;Folkes, Koletsky, and Graham 1987) leading to retaliatory behavior (Andreassen 1999;Harrison-Walker 2012). To our knowledge, existing work has not examined how attributions may influence positive reactions to firms, such as increased empathy or compassion.…”
Section: Perceptions Of Fairnessmentioning
confidence: 99%
“…In addition to clarifying personality traits through the use of cultural indicators, research revealed that experiencing diff erent cultures plays an important role in understanding the communication process in multicultural contexts (Harrison-Walker, 2012). In multicultural structures, including those in the hospitality sector, a reinforced (cross-cultural) communication process enhances customer satisfaction and improves relational exchange among employees (Harrison-Walker, 2012;Ihtiyar & Ahmad, 2014). This contributes to the better understanding and prediction of customer behaviors in a multicultural service environment (Wu & Chen, 2015).…”
Section: Multicultural Personality Traitsmentioning
confidence: 99%
“…This contributes to the better understanding and prediction of customer behaviors in a multicultural service environment (Wu & Chen, 2015). In other words, in multicultural service environments, service providers should consider the personalities and communication processes of their employees and customers to increase positive customer experiences (Harrison-Walker, 2012;Ihtiyar & Ahmad, 2014;Wu & Chen, 2015).…”
Section: Multicultural Personality Traitsmentioning
confidence: 99%
“…Nevertheless, while the body of research suggests the important role played by service environment designs on consumer emotions and behavioral intentions (Pullman & Gross, ; Petzer, De Meyer, Svari, & Svensson, ; Sengupta, Balaji, & Krishnan, ), insights into whether service designs can influence consumers' responses after service failures remain unknown. Service failures occur when providers fail to meet consumers' expectations (Zeithaml, Berry, & Parasuraman, ), generating adverse effects on consumer behavior (e.g., Bonifield & Cole, ; Harrison‐Walker, ; Reynolds & Harris, ). From a practical standpoint, service failures cost businesses around $62 billion per year due to the loss of disappointed clientele (Forbes, ).…”
Section: Introductionmentioning
confidence: 99%